Fertility in four regions spanning large contrasts in serum levels of widespread persistent organochlorines: a cross-sectional study - Bonefeld-Jørgensen Eva C; Manicardi Gian; Spano Marcello; Zinchuk Andery; Zvyezday Valentina; Ludwicki Jan K; Pedersen Henning; Rignell-Hydbom Anna; Thulstrup Ane; Giwercman Aleksander; Axmon Anna; Toft Gunnar; et al. (BMC, 2005)
Abstract Background Persistent organochlorine pollutants (POPs) may interfere with reproductive function but direct evidence in humans is very limited. Methods Fertility was examined in four regions with contrasting blood levels of POPs. Pregnant women and their partners in Warsaw (Poland), Kharkiv (Ukraine) and Greenland were consecutively enrolled during antenatal visits. Swedish fishermen and their spouses were recruited separately and independently of current pregnancy. Lipid adjusted serum concentrations of 2,2',4,4',5,5'-hexachlorobiphenyl (CB-153) and 1,1-dichloro-2,2-bis (p-chlorophenyl)-ethylene (DDE) were available for both partners. Time to pregnancy interviews were obtained among 2269 women and 798 men provided a semen sample. Results Inuits had high levels of both POP markers, Swedish fishermen were high in CB-153 but low in DDE, men from Kharkiv were high in DDE and low in CB-153 while men from Warsaw were low in CB-153 and had intermediate DDE levels. Compared to Warsaw couples, fecundability was reduced among couples from Kharkiv [adjusted fecundability ratio (FR) 0.64 (95% CI 0.5-0.8)] and elevated in Swedish fishermen families [FR 1.26 (95% CI 1.0-1.6)]. Adjusted geometric means of sperm counts and morphology did not differ between regions while sperm motility was higher in men living in Warsaw. Conclusion We observed regional differences in time to pregnancy and sperm motility that may be related to regional differences in POP blood levels, but other interpretations are also plausible. In particular, differences in access to safe contraception and in the prevalence of contraceptive failures are most likely to bias comparisons of time to pregnancy.